Cooperative learning following the CA/AC methodology A case study - Riera Romero, Gemma; Bosch Sanfelix, Mercé (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The article we present focuses on the methodology of cooperative learning to promote the inclusion of all pupils. Here, we take as a reference the work done in different investigations linked to the implementation of a didactic programme to work on cooperative learning in the classrooms: The programme “cooperating to learn/learning to cooperate”; as well as the training and advisory processes we have carried out in this field to date.